Increasing Retention of Nurses in Hospital Through Compensation Strategies - Sutanto, Martin; Purwati, Wahyuni Dian; Pamungkas, Rian Adi (Alta Dharma Publisher, 2023)
Background: Low nurse retention has a negative impact on hospital performance and effectiveness. Objective: The study examines the effect of the compensation system and works motivation on nurse retention mediated by organizational commitment. Method: A quantitative study with a cross-sectional approach was applied in this study. The sample in this study was nurses with a working period of more than one year. Path analysis is used to analyze the data. Result: The results showed that simultaneously there was an influence of the compensation system, work motivation, and organizational commitment on the retention of nurses with organizational commitment as an intervening. Partially the compensation system and work motivation have a positive and significant effect on the retention of nurses. Conclusion: The direct impact of the compensation system and work motivation on nurse retention is more critical than that mediated by organizational commitment. Recommendations: The compensation system, work motivation, and organization need to be considered to increase the retention of nurses working at hospitals. Further studies must examine more variables to ensure the factors associated with nurses' retention